POSTMODERN: PRO ET CONTRA. SOCIO-HISTORICAL AND CULTUROLOGICAL DISCOURSE IN THE 1950s-1980s. - Tetyana V. Danylova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen', 2013)
Purpose. This article attempts to explore the establishment of socio-historical and culturological discourses of postmodern in the 1950s-1980s. Methodology. Author use the method of philosophical hermeneutics. Scientific novelty is reflected in the results from a comparative analysis of the socio-historical and cultural discourses of postmodern in the 1950s-1980s. Practical value of this paper consists in the development of insufficiently studied subject, which attempts to describe post-nonclassical discourse itself and a new understanding of human as a part of this discourse. Conclusions. As can be seen, the discourse of postmodern is a response to social and economic development. In the 1980s discussions about the complete break with the modern discourse started. Advocates of the postmodern urged to create and develop new theories, values, modes of writing, etc. Time will tell what will be post postmodern.